Ultrastructural changes in the thyroid gland under prolonged monosodium glutamate exposure and after its withdrawal - Svyatotska , L.O.; Mateshuk-Vatseba , L.R. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The thyroid gland is an endocrine organ whose hormones regulate metabolism, growth, development, thermoregulation, and the functions of the nervous, cardiovascular, and reproductive systems. Monosodium glutamate (MSG; E621) is widely used as a flavor enhancer and, although generally considered safe, prolonged or high-dose consumption may exert toxic effects on various organs, including the thyroid gland. Objective. To evaluate the ultrastructural changes in thyroid follicular cells (thyrocytes) of Wistar rats under prolonged MSG exposure and after its withdrawal in an experimental setting. Materials and methods. Male Wistar rats were divided into seven experimental groups with different durations of MSG administration (4, 8, 10, 10+2, 12, 10+4, and 14 weeks) and a control group. MSG was administered orally at a dose of 0.07 g/kg/day. Thyroid glands were fixed in OsO₄, contrasted with uranyl acetate, polymerized in epoxy resin, and ultrathin sections were prepared for examination using a PEM-100 electron microscope at magnifications of 3200–8000×. The ultrastructural features of nuclei, mitochondria, endoplasmic reticulum, Golgi apparatus, secretory granules, and microvilli were analyzed. Results. Prolonged MSG exposure caused progressive ultrastructural alterations in thyrocytes, including mitochondrial swelling, cytoplasmic vacuolization, deformation of microvilli, expansion and vacuolization of endoplasmic reticulum cisternae and Golgi apparatus, and reduction in the number of secretory granules. The severity of these changes increased with the duration of MSG exposure, reaching marked dystrophic manifestations in groups with 12–14 weeks of treatment. Following MSG withdrawal, partial restoration of cellular structure was observed; however, signs of sublethal damage persisted. Conclusions. Prolonged MSG administration induces significant ultrastructural changes in thyroid follicular cells. MSG withdrawal contributes to partial recovery, but the persistence of subcellular damage indicates potential long-term functional impairments. These findings highlight the need for further assessment of MSG safety and investigation of its long-term effects on endocrine organs.